Successful treatment of an invasive fungal infection caused by Talaromyces sp. with voriconazole - BİLGİN, HÜSEYİN; ÇİMŞİT, NURİ ÇAGATAY; SİLİ, ULUHAN; KORTEN, VOLKAN (ELSEVIER SCIENCE BV, 2015)
Invasive fungal infections (lFl) are on the rise due to increasing numbers of immunosuppressed and critically ill patients. A malignant-looking pulmonary nodule in an immunosuppressed patient may indeed be caused by a fungal organism. We report a patient, who was eventually diagnosed with an IFI caused by an agent of hyalohyphomycosis, Talaromyces sp determined via molecular methods and succesfully treated with voriconazole. (C) 2015 The Authors, International Society for Human and Animal Mycology Published by Elsevier B.V.
Keywords: Invasive fungal infection; Rheumatoid arthritis; Mold infection; Voriconazole; IDENTIFICATION